Comparative genomics of Bacillus cereus sensu lato spp. biocontrol strains in correlation to in-vitro phenotypes and plant pathogen antagonistic capacity - Moshe, Maya; Gupta, Chhedi Lal; Jain, Rakeshkumar Manojkumar; Sela, Noa; Minz, Dror; Banin, Ehud; Frenkel, Omer; Cytryn, Eddie (Frontiers in Microbiology, 2023)
Bacillus cereus sensu lato (Bcsl) strains are widely explored due to their capacity to antagonize a broad range of plant pathogens. These include B. cereus sp. UW85, whose antagonistic capacity is attributed to the secondary metabolite Zwittermicin A (ZwA). We recently isolated four soil and root-associated Bcsl strains (MO2, S-10, S-25, LSTW-24) that displayed different growth profiles and in-vitro antagonistic effects against three soilborne plant pathogens models: Pythium aphanidermatum (oomycete) Rhizoctonia solani (basidiomycete), and Fusarium oxysporum (ascomycete). To identify genetic mechanisms potentially responsible for the differences in growth and antagonistic phenotypes of these Bcsl strains, we sequenced and compared their genomes, and that of strain UW85 using a hybrid sequencing pipeline. Despite similarities, specific Bcsl strains had unique secondary metabolite and chitinase-encoding genes that could potentially explain observed differences in in-vitro chitinolytic potential and anti-fungal activity. Strains UW85, S-10 and S-25 contained a (~500 Kbp) mega-plasmid that harbored the ZwA biosynthetic gene cluster. The UW85 mega-plasmid contained more ABC transporters than the other two strains, whereas the S-25 mega-plasmid carried a unique cluster containing cellulose and chitin degrading genes. Collectively, comparative genomics revealed several mechanisms that can potentially explain differences in in-vitro antagonism of Bcsl strains towards fungal plant pathogens.